A study of some morphological characteristics of the Tigris River in the city of Baghdad (Journal of the College of Education for Women, 2019)
Change the morphological characteristics with the change of the factors affecting it has been shown that the Tigris River has the characteristics of the morphology of the low values in terms of depth, width and perimeter wet and gradient which in turn affected the morphological and other characteristics in terms of the direction and pattern of runoff came through the study of 48 cross-section is taken of the Tigris River Year 2008 by section for each 1 km, it has been shown that the average width of the Tigris River does not exceed 221.1 meters and the average depth of 3.9 meters either wet ocean amounted to 268.9 meters and changed the cross-section area of the last section at a rate of 4594.3 square meters, and through the study turned out to be the second part of the river is the lowest in the morphological values in terms of depth, width and cross-sectional area, it has been shown that the Tigris River with low efficiency in terms of the ability of the Hungarian maintain the amount of water contained and these characteristics do not accommodate drainage extraordinary2